VARIASI BAHASA PADA INTERAKSI PENJUAL DENGAN PEMBELI DALAM TRANSAKSI JUAL BELI DI PASAR SAYUR PADANGPANJANG: KAJIAN SOSIOLINGUISTIK - Pohan, Ratna Sari Dewi; Fitri, Laila; Arzanto, Arya Gilang; Yuhelmi W., Yuhelmi W. (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Language variations are divided into four categories: variations based on the speaker, variations based on usage, variations based on formality, and variations based on means and media. This study focuses on language variations based on the speaker. This research is motivated by the fact that many people still do not understand the concept of language variation and the reasons behind their use of such variations. Language variation also plays a significant role in interactions, particularly in buying and selling transactions. The aim of this study is to analyze the language variations that occur in the interactions between sellers and buyers at the vegetable market in Padangpanjang. This study employs a descriptive qualitative method. Data collection was conducted using the observation method with non-participant observation, recording, and note-taking techniques. The steps of analysis included the following stages: 1) watching the research video, 2) classifying the data based on the type of language variation, 3) describing the data, 4) analyzing the data, and 5) drawing conclusions. The results of the analysis show that the types of language variation found based on the speaker are classified into idiolect, dialect, chronolect, and sociolect. The research data consisted of 68 utterances. Based on the classification, the utterances were found to be: 24 idiolect utterances, 39 dialect utterances, 2 chronolect utterances, and 3 sociolect utterances.Keywords: Language variations, idiolect, dialect, chronolect, sociolect